Probabilistic Model of Onset Detection Explains Paradoxes in Human Time Perception - Nikolov, Stanislav; Rahnev, Dobromir A.; Lau, Hakwan C. (Frontiers in Psychology, 2010)
A very basic computational model is proposed to explain two puzzling findings in the time perception literature. First, spontaneous motor actions are preceded by up to 1-2 s of preparatory activity (Kornhuber and Deecke, 1965). Yet, subjects are only consciously aware of about a quarter of a second of motor preparation (Libet, 1983). Why are they not aware of the early part of preparation? Second, psychophysical findings (Spence, 2001) support the principle of attention prior entry (Titchener, 1908), which states that attended stimuli are perceived faster than unattended stimuli. However, electrophysiological studies reported no or little corresponding temporal difference between the neural signals for attended and unattended stimuli (McDonald et al., 2005; Vibell et al., 2007). We suggest that the key to understanding these puzzling findings is to think of onset detection in probabilistic terms. The two apparently paradoxical phenomena are naturally predicted by our signal detection theoretic model.